Evaluation of Neem Seed Water Extract, Biobit and Karate on Insect Abundance and Yield of Local Garden Egg (Solanvm Integrifolium L.) - Owusu-Ansah, F. (University of Ghana, 1999)
The effect of Neem Seed Water Extract (NSWE) on insects and growth performance of eggplant (local garden egg) was evaluated in the field from June to October 1998 at Ekoso in the Eastern region, Ghana. The extract was applied at the rate of 75 g of seed per litre of water and compared with a standard insecticide (Karate), a registered Bacillus thuringiensis Berl. (Biobit) and water only as control. The effect of each treatment on leaf, shoot and fruit damage caused by defoliators, shoot, bud, and fruit borers were determined. The influence of the treatments on plant biomass and other vegetative growth indices such as plant height, plant girth, number of functional leaves and branches per plant, flower production as well as fruit yield were also assessed. Water traps were used to monitor the effects of the various treatments on the abundance of insects associated with the crop. Economic benefits of each pesticide-use programme based on crop value, cost of pest control and net profits were determined. Karate and NSWE treatments significantly (P<0.05) reduced percentage fruit damage, number of borers per fruit and defoliation. Although NSWE could not effectively control shoot and bud borers as Karate, it performed better (P<0.05) in reducing percentage borer damage than either Biobit or control. The neem seed extract significantly (P<0.05) promoted vegetative growth than the rest of the treatments, but delayed flower initiation. Fruit yield per plant did not differ significantly (P>0.05) among Karate, NSWE and Biobit treatments. All three treatments, however, produced higher yields than the control plots with Karate-treated plots recording numerically higher yield followed by NSWE. Net profit obtained from Karate treatment was higher ((211,187,772.00) per hectare compared with that of NSWE treatment ((£8,747,772.00). However, NSWE performed better than Biobit, which recorded a net profit of (£6,283,852.00/ha. Control plot had the least net profit of ct5,752,772.00/ha. Insects from seven major orders (Coleoptera, Lepidoptera, Odonata, Orthoptera, Diptera, Hymenoptera and Hemiptera) were found associated with the local garden egg. Fewer numbers of predators, mainly hymenopterans, were collected from plants treated with Karate compared to either NSWE- or Biobit- treated plots. This indicates that Karate had adverse effects on beneficial insects in the garden egg ecosystem. The major pest complex of garden egg included Leucinodes orbonalis Guen. which attacked the shoots and fruits, the bud borer Scrobipalpa blapsigona Meyrick, Pachnoda spp. which scraped and chewed stem and defoliators comprising Acraea peneleos peneleos Ward., A. pharsalus pharsalus Ward., Zonocerus variegates L., Eulioptera spp. and Phaneroptera nana Stal. Neem seed water extract can be used as alternative to synthetic insecticide for the control of local garden eggs by resource poor farmers.
Thesis(M Phil)-university of Ghana,1999.